Diel and annual rhythms of tropical stem size changes in the Mayombe forest, Congo Basin - Luse Belanganayi, Basile; Ilondea, Bhely Angoboy; Phaka, Christophe Mbungu; Laurent, Félix; Djiofack, Brice Y.; Kafuti, Chadrack; Peters, Richard L.; Bourland, Nils; Beeckman, Hans; De Mil, Tom (Frontiers in Forests and Global Change, 2024)
The Congo Basin forests, a crucial global carbon sink, are expected to face increased challenges of climate change by 2027, with an expected temperature rise of 1.5°C above pre-industrial levels, accompanied by increased humidity conditions. However, studies that try to understand their functioning and untangle the species-specific responses about how weather conditions impact secondary growth dynamics are still rare. Here we present the results of a study on diel and seasonal stem growth in 17 trees, belonging to 11 most abundant species, both canopy and understory, in the Mayombe forest (Congo Basin) in the Democratic Republic of the Congo (DRC). We measured highly-resolved radial stem size variations and weather conditions, to comprehend the ongoing patterns of secondary growth and examine the potential influence of projected weather conditions on them. We found that at the diel scale, trees probably grow mainly from 6pm to 9am, and that at the annual scale, they grow mainly during the rainy season, from October to May. Some trees grow year-round, while others stop growing for a period ranging from 1 to 4 months. This growth cessation typically occurs during the dry season from June to September. A generalized linear mixed-effect model revealed that annual radial stem growth is positively related to rainfall. Our results suggest that trees in the study site have a significant potential to cope with the projected 1.5°C increase in global temperature and an additional 50 mm of local rainfall. Trees of the species T. superba exhibited improved growth under the projected scenarios, showing continuous year-round growth. For the other tree species, no significant difference in growth was observed between the predicted and observed scenarios. We believe that much remains to be done to better understand the tree growth-climate interaction of the large variety of tree species in the Congo Basin.